Volume of fluid simulation of isothermal viscous spreading flows - Perrier,H; Eaton,M; Wachem,BV (2017)
© 2016 Association for Computing Machinery Inc. All Rights Reserved. The spreading of an isothermal dense viscous liquid into a gas environment was investigated using Computational Fluid Dynamics (CFD) simulations. A Volume of Fluid (VOF) method was used to model the two-phase liquid/gas system. It was noticed that due to the use of VOF methods, a layer of gas could be trapped below the liquid front forming a “gas cushion”. This effect was described and a solution to prevent it using a Navier-Slip boundary condition at the wall was proposed. The influence of the Navier-Slip condition, numerical parameters, physical models and fluid properties on the spreading behavior was studied and simulation guidelines were proposed.